The genus Ctenothrips from India (Thysanoptera: Thripidae) with description of one new species and one new record - Tyagi, Kaomud; Ghosh, Biswatosh; Kumar, Vikas (Zootaxa, 2014)
Ctenothrips barapatharensis sp.n. is described from specimens collected on ferns from Himachal Pradesh state of India. This is the only species in this genus having dark thickenings attached to fore ocellus. Ctenothrips niger Kudô is newly recorded from India, and the brachypterous form is described for the first time. A key to the three species of Ctenothrips from India is provided.